KUALITAS PELAYANAN RECEPTIONIST DI HOTEL NOVOTEL PEKANBARU - Purba, Tiona; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aimed to determine the quality of service at the Novotel Pekanbaru Hotel, especially services at the front office department section receptionist. This study aims: (1) to find out how guests' perceptions of the quality of receptionist services at the Novotel Hotel Pekanbaru, (2) to determine the efforts made by management to improve the quality of receptionist services at the Novotel Pekanbaru Hotel. The samples used in this study were 100 people, the sampling technique was determined using accidental sampling technique, this study used a quantitative descriptive method to examine the issues raised in this study. The results of this study indicate that the quality of receptionist services at Hotel Novotel Pekanbaru has been running optimally, this can be seen from the responses of respondents who rated each dimension of service quality as good. Therefore Hotel Novotel Pekanbaru must further maintain and further enhance each of the dimensions of service quality, both in the dimensions of tangibles, empathy, reliability, responsiveness and assurance as well as finding new findings that can improve the quality of front office services, especially at receptionists.Keywords: Service Quality, Tangible, empathy, reliability, responsiveness and assurance, Front Office, Receptionist